THE PSYCHOANALYTIC STUDY OF EMMA BOVARY IN GUSTAVE FALUBERT’S MADAME BOVARY - Sumarsono, Irwan (Lingua, 2019)
This study presents the psychoanalytic analysis of Gustave Flaubert’s Madame Bovary. The adultery conducted by the main female character of the novel is the center of the study that is analyzed by using Freud’s psychoanalysis. The study uses the psychoanalysis theory to analyze how the id, ego and superego influence the main character in committing the adultery, and the reasons of the female character’s adultery in the novel. It is found that the female character’s id controls her adultery very much that drives her to conduct it.